Production of electroplated Co-Al2O3 nanocomposites by pulse reverse plating (PRP) and anionic surfactant. (4th July 2019) - Albusalih, D.; Gill, S.; Weston, D.; Altmann, F.
ABSTRACT: Nanocomposite Co-Al2 O3 electrodeposited coatings have been produced for the first time by pulse reverse plating (PRP) in conjunction with an anionic surfactant, sodium dodecylsulphate (SDS), by a similar method used for Co – IF WS2 deposition in previous work. The influence of two parameters on nanocomposite composition and morphology was investigated in this study: the SDS content of the bath was varied (from 0 to 0.8 g L −1 ) as well as the length of the cathodic pulse, from t c  = 30 s to 120 s. In addition, the composites were also produced by direct current (DC) for comparison. Co-PTFE nanocomposites were also considered using the same approach. The coatings were characterised microstructurally by SEM, EDX, XRD, and mechanically with a Knoop microhardness test. For Co-Al2 O3, the alumina particle content is high for PRP coatings compared to those produced by DC; a higher particle content was achieved at lower t c . Increasing SDS led to a peak in the particle content, followed by a reduction in the particle content with further increase in the SDS concentration. Cathode efficiency decreased with increasing t c, but is higher compared to the DC coatings. Particle surface coverage for both nanocomposites per pulse cycle follows a pattern for the PRP coatings with varying SDS content that is different to that achieved with DC coatings. Increasing particle content led to a decrease in crystallite size, which indicated that the particle inclusion led to grain size refinement. However, analysis of the hardness tests showed that the Al2 O3 particles predominantly provide dispersion strengthening. For Co-PTFE the PRP mechanism was shown to be ineffective in producing composite coatings. This is thought to be due to the larger size of the particle.